2009
DOI: 10.1016/j.jbiomech.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Tibiofemoral kinematics and condylar motion during the stance phase of gait

Abstract: Accurate knowledge of the dynamic knee motion in vivo is instrumental for understanding normal and pathological function of the knee joint. However, interpreting motion of the knee joint during gait in other than the sagittal plane remains controversial. In this study, we utilized the dual fluoroscopic imaging technique to investigate the six-degree of freedom kinematics and condylar motion of the knee during the stance phase of treadmill gait in eight healthy volunteers at a speed of 0.67m/sec. We hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

54
241
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(302 citation statements)
references
References 48 publications
54
241
7
Order By: Relevance
“…The rotation of the femur with respect to the tibia varies during gait with twin peaks of external rotation being observed during early midstance and toe-off [50]. The same study demonstrated twin peak of valgus at similar points of the stance phase [50]. It is interesting to note this corresponds with the twin peaks of load measured in dogs during gait [29].…”
Section: Combined Compression and Shearmentioning
confidence: 52%
See 2 more Smart Citations
“…The rotation of the femur with respect to the tibia varies during gait with twin peaks of external rotation being observed during early midstance and toe-off [50]. The same study demonstrated twin peak of valgus at similar points of the stance phase [50]. It is interesting to note this corresponds with the twin peaks of load measured in dogs during gait [29].…”
Section: Combined Compression and Shearmentioning
confidence: 52%
“…Both compartments demonstrated a cartilage contact deformation of between 10% and 15% and the bulk of this deformation was generated during the first 20 seconds of load [37]. The rotation of the femur with respect to the tibia varies during gait with twin peaks of external rotation being observed during early midstance and toe-off [50]. The same study demonstrated twin peak of valgus at similar points of the stance phase [50].…”
Section: Combined Compression and Shearmentioning
confidence: 70%
See 1 more Smart Citation
“…In vivo contact forces and joint motions are essential for patient-specific wear prediction [6]. Although in vivo knee contact forces and joint motions have been measured using instrumented knee prostheses [22,23] and fluoroscopic imaging system [24] respectively, it is still difficult to obtain all these information from the same patient simultaneously. Consequently, multibody dynamics (MBD) modelling of TKR by considering the patient-specific lower extremity musculoskeletal (MSK) system is an alternative attractive method to the in vivo measurements [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is not clear what happens in a pathological joint-if the bone glides too little or too much and in which direction-and maybe in functional activities, such as walking and running, even in healthy subjects the pattern could be different. 4,8 So, as manual therapists, it could be important to focus on these 2 aspects in future research, to understand which direction of translation is more effective in some specific disorders.…”
mentioning
confidence: 99%